Adaptation Gap Report 2023 - Global progress on adaptation implementation - Njuguna, Lucy (2023)
As the impacts of climate change become more extreme, understanding progress in adapting to climate change is critical. This presentation provides an overview of the 2023 Adaptation Gap Report, with special attention to progress in adaptation implementation. The presentation was made at the ILRI Sustainable Livestock Systems weekly seminar on November 20, 2023.